Wedding Genre in the Works of Composers of the Kyiv Choral School Early XX Century - Zasadna, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2020)
Relevance of the study is in need to open and comprehend the whole palette of genres of spiritual music, which were created in the first third of the twentieth century at the request of the newly established Ukrainian Autocephalous Orthodox Church, the important role of the study of the act of “Wedding” embodied in the creative works of the writings of Ya. Yatsynevych, O. Koshits, Y. Kozitsky. The objective of the study is to highlight the processes related to the Ukrainianization of the Divine Service during the period of Ukrainian Church revival in the first third of the twentieth century. The choral cycles of the aforementioned composers have been analyzed for the embodiment of the general principles declared by the Commission for the Ukrainization of the Divine Service, December 4, 1918, during the Third Session of the All-Ukrainian Orthodox Church Council, where it was said, that build a church melody from them. So, we see that updating the liturgical genres, in line with the national musical language, was a top priority for artists. They were called to show the differentness of Ukrainian spiritual music from the Russian, which then prevailed in the church space. The source for these searches were ancient songs of the Ukrainian church, folk songs and paralytic creativity: cantos, psalms, devotional songs. Metodology is based on general scientific methods of research – historical, systematicanalytical, textual and source studies, implemented with the help of historical-retrospective, genre-style and functional approaches. The need for illumination of the social-church context led to the application of an interdisciplinary approach with the use of synthesis of cultural and musical-liturgical analyzes. Due to the fact that liturgical creativity of Ukrainian artists, and especially the sphere of paralytic genres, is marked by an extremely high level of use of folklore factors in the stylistic system, the methods of study of various works belong to both those inherent in canonical church creativity and those used to study secular choral music. This approach revealed in the musical texts certain stylistic models of different genesis, which are marked by a bright national stylistic specificity. A well-researched, stylistic, performing analysis of each song is performed separately and in the context of the cycle, in order to summarize the general principles of the development of spiritual choral music of that time. The significant influence of the liturgical act of “Marriage” on the structure, form and content of both individual songs and cycles as a whole is revealed. The main results will contribute to the deepening of knowledge about Ukrainian choral art of the 1920s, their significance opening up a new frontier in the field of sacred music.